Drug Injection-Related and Sexual Behavior Changes in Drug Injecting Networks after the Transmission Reduction Intervention Project (TRIP): A Social Network-Based Study in Athens, Greece - Giallouros, George; Pantavou, Katerina G.; Pampaka, Despina; Pavlitina, Eirini; Piovani, Daniele; Bonovas, Stefanos; Nikolopoulos, Georgios K. (My University, 2021)
The Transmission Reduction Intervention Project (TRIP) was a network-based, enhanced contact tracing approach, targeting recently HIV-infected people who inject drugs (PWID) in Athens, Greece (2013-2015). This analysis examines behavioral changes of participants in TRIP and their determinants between baseline and follow-up visits to the program. All participants of TRIP were tested for HIV and interviewed using a questionnaire with items on drug injection-related and sexual behaviors. Multivariable logistic regression models were used to examine potential relationships between participants' behaviors and sociodemographic or other characteristics. The analysis included 292 participants. At follow-up, the percentage of participants who injected drugs decreased [92.5%, n = 270 versus 72.3%, n = 211 (p < 0.001)], and more participants adopted safer behaviors. Employment, age, and gender were significantly associated with some behavioral changes. For instance, unemployed participants were half as likely as the employed to stop drug injection [adjusted odds ratio (aOR): 0.475, 95% confidence interval (CI): 0.228, 0.988]. Increasing age was associated with lower probability of sharing syringes at follow-up (aOR: 0.936, 95%CI: 0.887, 0.988). Finally, females were less likely than males to improve their behavior related to sharing cookers, filters, or rinse water (aOR: 0.273, 95% CI: 0.100, 0.745). In conclusion, adoption of safer behaviors was observed following TRIP implementation. Future prevention programs should focus on younger PWID and especially females. Social efforts to support employment of PWID are also important.
Keywords: HIV; PWID; Injecting-related behaviors; Networks; Recent infection; Sexual behaviors